OPTIMALISASI KINERJA BANK PERKREDITAN RAKYAT SYARIAH INDONESIA: WAWASAN DARI FAKTOR INTERNAL - Setiawan, Setiawan (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2024)
This study aims to analyze the impact of financing risk, efficiency, liquidity, and capital adequacy on the performance of Islamic Rural Banks (BPRS) in Indonesia. BPRS performance is measured using Return on Assets (ROA), while financing risk is proxied by Non-Performing Financing (NPF), efficiency by the Operating Expenses to Operating Income ratio (BOPO), liquidity by the Financing to Deposit Ratio (FDR), and capital adequacy by the Capital Adequacy Ratio (CAR). This research uses secondary data from the annual reports of BPRS during the 2019–2023 period, with a total of 760 unbalanced panel data observations. The data analysis technique employed is Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that financing risk (NPF) and efficiency (BOPO) have a significant negative effect on BPRS performance. Meanwhile, liquidity (FDR) shows no significant effect on performance. Capital adequacy (CAR) has a significant but inverse effect on BPRS performance. These findings indicate that financing risk management and operational efficiency are critical determinants in improving the profitability of BPRS. Furthermore, more strategic capital management is needed to ensure its effectiveness in supporting bank performance.